Research on Key Factors of Sealing Performance of Combined Sealing Ring - Heming Cheng; Xinyuan Chen; Xiaolan Chen; Hucheng Liu (Applied Sciences, 2022)
In this study, the mechanical properties of a combined seal ring under different loads were numerically calculated using ANSYS. The effect of the working pressure and pre-compression ratio of a rubber O-ring on the contact stress of the combined seal ring was studied. The influence of the wear ring’s chamfer, thickness, and width on the contact stress and contact force of the combined seal ring was analyzed. Studies have shown that it is particularly important to select a compression ratio that is suitable for the working conditions. Under the same conditions of working pressure and compression ratio, upon increasing the wear ring chamfer, the contact pressure is decreased due to the decreasing contact bandwidth between the wear ring and the cylinder wall. This has little effect on the contact stress of the combined seal ring as well as the contact force, while the width of the wear ring is proportional to the latter.